The effect of ethical leadership on subjective wellbeing, given the moderator job satisfaction (a case study of private hospitals in Mashhad) - Azar Kaffashpoor; Samaneh Sadeghian (BMC, 2020)
Abstract Background The emerging ethical leadership, a unique approach in leadership viewpoint, has provided the ground for constructing and advancing individual and managerial efficiency by highlighting ethics in organizations. The present study aims to investigate the influence of Ethical Leadership on Subjective Wellbeing, Given the Moderator Job Satisfaction in Private Hospitals in Mashhad. Methods This descriptive-correlational research design stud was conducted in 2015-2016 to inspect the possible effect of ethical leadership on subjective wellbeing and job satisfaction, as dependent and mediator variables, among the Iranian private hospitals' nurses in Mashhad. Simple random sampling method was used to select the sample of 166 nurses out of the population of 730 nurses, in total. The valid and reliable adapted version of the questionnaire designed by Yang (2014) was used to collect the data, and structural equation modeling (SEM) was used to analyze the data set. Results The results showed that there is a positive significant correlation between ethical leadership and job satisfaction. More specifically, the findings indicated that Ethical leadership affected the subjective wellbeing of nurses through job satisfaction both directly and indirectly. Conclusions The findings illustrated that focus on ethics and ethically-oriented leaders in hospitals, enriched by job satisfaction can lead to the nurses' subjective wellbeing by providing them a positive climate.